PEMANFAATAM MEDIA FLIP CHART UNTUK PENGUATAN LITERASI SAINS SISWA SMP PADA MATERI PENCEMARAN LINGKUNGAN - Yen Sastri; Evi Suryawati; Mariani Natalina, L (Program Studi Pendidikan Biologi, 2021)
This research aims to determine the effect of using flip chart on students' scientific literacy on environmental pollution material. This development research used ADDIE model. This research was carried out until the development phase. The flip chart that have been produced validated by using validation sheets by 4 validators who expert on media and material, then tested on 20 grade VIII junior high school student. The data of Students’ responses about flip chart were collected by using a questionnaire and students’ science literacy were collected by using multiple choice test. The results of the research indicated that Flip Chart was valid with score 88,3% (very valid) in material and 87,5% (very valid) in media. The result of this result also indicated that there was an increase in the mean score of pre-test and post-test from 62 (low) to 81 (high). It illustrated that there was a strengthening of science literacy on the competence to explain phenomena scientifically from 61.25% (low) to 87.5% (very high), the competence to design and evaluate scientific enquiry from 53.75% (low) to 71.25% (enough), and the competence to interpret data and evidence scientifically from 80% (high) to 87.5% (very high). This result was supported by student questionnaires when using flip chart, which is 88.1, it shows that flip charts can be used as a means of strengthening student scientific literacy.